Esmolol Administration for the Treatment of Refractory Ventricular Fibrillation - KARAASLAN, KAZIM; Karaaslan, KAZIM; AY, YASİN; UMUTOGLU, Tarik; TOPUZ, Ufuk; Ay, YASİN (My University, 2016)
Ventricular fibrillation (VF) after releasing an aortic cross clamp in patients undergoing open heart surgery procedures is not rare. Ischemiareperfusion injury after release of the aortic clamp, increased adrenergic tone, and insufficient protection of the myocardium are the possible causes. Amiodarone, lidocaine, and beta blockers have been added to the cardioplegia solutions as a preventive measure for reperfusion VF. We report a case of life-threatening, shock-resistant VF during the weaning period of a cardiopulmonary bypass (CPB) in a 61-yearold male who underwent a mitral valve repair surgery for mitral valve regurgitation. After several defibrillation attempts, refractory VF was turned to normal sinus rhythm shortly after ultra-short acting, beta blocking agent esmolol administration. CPB was terminated successfully following this. In conclusion, VF is still a major problem for clinicians and the treatment of refractory VF is not well defined. In contrast with the absence of the sufficient randomized controlled human studies, theoretically beta blockers could be a choice alternative for shock refractory VF.
Keywords: Esmolol; Refractory; schock resistant; beta blocker; VF